Pengaruh NOM, BOPO dan FDR terhadap Profitabilitas pada Bank Umum Syariah (BUS) Periode 2021-2023 - Aviva Refalina; Hilda Hilda; Riduwansah Riduwansah (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Profitability is a key indicator in assessing the financial performance and operational sustainability of a bank. However, during the 2021-2023 period, the Islamic banking industry in Indonesia faced various challenges, especially regarding operational efficiency and financing management. This challenge can be seen from the unstable value of the Net Operating Margin (NOM), the high ratio of Operating Expenses to Operating Income (BOPO), and the imbalance in the Financing to Deposit Ratio (FDR). This study uses a quantitative approach with secondary data from the annual financial statements of Islamic Commercial Banks for the 2021-2023 period which are accessed through the OJK official website. The object of research includes all Islamic Commercial Banks operating during this period, with a sample of 10 banks selected through purposive sampling method. The data were analyzed using IBM SPSS version 30.0 in 2024 with descriptive statistical analysis techniques, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination (R²) tests. The results of this study indicate that partially the Net Operating Margin (NOM) variable has a significant effect on Profitability (ROA). While the variable Operating Cost of Operating Income (BOPO) and Financing to Deposit Ratio (FDR) has no effect on Profitability (ROA).